Negosiasi Identitas Budaya Jawa pada Penerjemahan Deiksis Sosial dari Novel Rumah Kaca ke dalam Bahasa Prancis - Rahmadhani, Rizky Kurnia; Sajarwa, Sajarwa (Humanis; Vol 28 No 3 (2024)DO - 10.24843/JH.2024.v28.i03.p01, 2024)
Cultural identity negotitations are proven to occur in translation because translation is a form of cross-culture communication. The pupose of this research is to explore the negotiation of Javanese cultural identity through translating social deixis in French based on form, meaning and function. Under the descriptive-qualitative method, this research attempts to explore in-depth knowledge about the research object. The comparative method is used to find similarities and differences in the form, meaning and function of social deixis from the novel Rumah Kaca (1988) and its translation in French from the novel La Maison de Verre (2018). Negotiation of Javanese cultural identity can take the form of partial negotiations and full negotiations. The causes of negotiation are differences in language systems, prioritizing equivalence of social deixis function, and differences in cultural perspective. These causes have some impacts for equivalence, namely: partial equivalence and distortion of meaning.